Review of Strategies for Modelling Beam-to-Column Connections in Existing Precast Industrial Rc Buildings - Sousa, Romain (2019)
In recent earthquakes, it has been observed that precast RC structures has shown, in several cases, a poor performance presenting damages on structural and non-structural elements, highlighting the vulnerability of industrial buildings. Beam-to-column connection was pointed as one of the main source of damage. Precast concrete buildings are common in the industrial parks. One-story industrial building constituted by a frame system of beams and columns, with hinged beam-to-column connection are the most common structural configuration. In this way, it is important to characterize this type of buildings to understand its seismic behavior in order to develop new methodologies and solutions for design this type of buildings and improve your performance. The presented work is focused on beam-tocolumn connections that play a determining role on precast structures. The proposed work is the review of the different strategies to model beam-to-column connections in a precast industrial RC building is presented. To perform the analyses, the structural software Opensees was chosen. Nonlinear static analyses were performed. The results are presented and discussed.